Breathing in the polyrhythmic city: A spatiotemporal, rhythmanalytic account of urban air pollution and its inequalities. (May 2022) - Walker, Gordon; Booker, Douglas; J Young, Paul
Inspired by Lefebvre's meditation on the rhythms seen from his apartment in Paris, we develop a novel rhythmanalytic account of urban air pollution, its breathing-in and impact in vulnerable bodies. We conceptualise urban air pollution as entwined in its making and consequence with the diverse rhythms of technologies, social practices and socio-temporal structures, environmental and atmospheric processes, bodily movements in space and time, and rhythmically constituted corporeality. Through this interdisciplinary account we position urban air pollution as integral to the 'beat' of the city, both a product of and constituent part of its evolving spatiotemporal form. We build on this foundation to develop a polyrhythmic conceptualisation of how certain places and lives are more dominated by pollution than others. Unequal patternings are made through the structuring effects of rhythmic repetition and by fatal intersections between the rhythms of polluted air and unequal capacities to avoid harmful breathing in and to resist the arrhythmic corporeal consequences that can follow. Understanding inequalities as manifest not within a static landscape of spatial relations, but in sets of unequally unfolding and structured polyrhythmic relations has implications for revealing patterns of inequality and for extending evidence-making more deeply into how rhythms intersect. Which and whose rhythms are to be intervened in are also considered as key ethical and political questions. We draw out implications for activism and community action, and identify the potential for bringing rhythmanalysis into productive engagement with broader environmental justice concerns, including in relation to recent COVID-19 experiences.